To study the impact of coronavirus pandemic on manufacturing sector in India - Dr. Yogesh Mahajan, (Design Engineering, 2021)
The Indian economy is undergoing significant field of growth in manufacturing with diverse businesses, including machinery and equipment production, metal and electrical goods, cement, materials for building and development, rubber and plastic items and automation technology. In 2018, the production sector accounted for about 16% of world GDP. The paper studies the impact of coronavirus pandemic on manufacturing sector in India and the impact on employment in India. The paper found that the manufacturing sector is highly affected by coronavirus pandemic and contractual employment is affected in India as labourers have moved to their native place due to coronavirus pandemic. The companies’ responses to this issue include the introduction of protection procedures, sanitation and sanitization methods, a updated sourcing policy, the incorporation of new vendors, the streamlining of their product portfolio, a more responsive evaluation of supply chain resilience, an analysis of disaster or emergency management plans. In this way manufacturing sector can cope with the coronavirus pandemic.